EXTERNAL AUDIT: A CASE STUDY IN COMPANIES COOPER-RUBI AND CRV INDUSTRIAL OF THE ALCOHOL AND SUGAR (CIPEEX, 2024)
THE CONSTANT CHANGES IN THE WORLD REQUIRE NEW PERSPECTIVES, NEW INVESTMENTS, NEW PARTNERSHIPS. AND WITH THAT COMES OPPORTUNITIES AND OFTEN IN ORDER TO TAKE ADVANTAGE OF OPPORTUNITIES, IT IS NECESSARY TO BE PREPARED TO WHAT IS EXPECTED. ORGANIZATIONS, IN MOST CASES, NEED TO BE WITHIN RULES AND REGULATIONS SO THAT THEY CAN CARRY OUT A CERTAIN ACTIVITY, OR SIGN ANY SPECIFIC CONTRACT. IN THIS LOGIC, AUDITING IS THE BRANCH THAT CARRIES OUT INVESTIGATIONS IN COMPANIES TO COMPARE HOW THE COMPANY IS CURRENTLY AND HOW IT SHOULD BE, WHETHER IN SOME SPECIFIC AREA, OR IN GENERAL, THE COMPANY AS A ALL. THE AUDIT CONSISTS OF CAREFUL AND SYSTEMATIC EXAMINATIONS, WHICH SEEK DUE TO EXISTING PROBLEMS OR IN A SPECIFIC WAY, DUE TO ERRORS OR FRAUD. TO THE COMPANIES STUDIED ARE SUGAR AND ALCOHOL PLANTS, ONE CALLED COOPER-RUBI, FROM THE CITY OF RUBIATABA-GO, AND THE OTHER CALLED CRV INDUSTRIAL, FROM THE CITY OF CARMO DO RIO VERDE-GO. THE PRESENT STUDY AIMS TO ANALYZE THE PERCEPTION OF TWO EMPLOYEES OF THE COMPANIES MENTIONED, BOTH IN THE TRANSPORT SECTOR AND MECHANIZATION OF EACH COMPANY, REGARDING THE EXTERNAL AUDIT THAT IS CARRIED OUT IN MENTIONED COMPANIES. QUALITATIVE RESEARCH WAS USED ADDRESSING THE RESEARCH OF FIELD, WHICH SOUGHT TO DEMONSTRATE THE RESULTS AND BENEFITS OBTAINED BY COMPANIES WITH EXTERNAL AUDITS. THE DATA COLLECTION USED WAS THE APPLICATION OF A QUESTIONNAIRE WITH OPEN SUBJECTIVE QUESTIONS COLLECTED DIGITALLY. OBTAINED AS A RESULT THAT BOTH COMPANIES BENEFIT FROM EXTERNAL AUDITING, SUCH SUCH AS ISO 9001 CERTIFICATION AND THE SIGNING OF CONTRACTS WITH THE COCA-COLA BRAND.
Keywords: External audit, Auditor, Systematic Examination, Standards.